Accelerating XML Query Processing on Views - Huang, Yin-Fu; Cho, Yu-Hsien (Informatica, 2017)
<span style="font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 新細明體; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">With the widespread use of the eXtensible Markup Language (XML), more and more applications store and query XML documents in XML database systems. Thus, how to efficiently process a query and find the specified patterns conforming the query from XML documents is a crucial issue. In this paper, some processing methods are employed on XML documents to improve document retrieval. First, a materialized view is built from an original document for each query. Then, on each materialized view, auxiliary structures such as T-Bitmap and indexes are also built to further accelerate query processing. Finally, four experiments are conducted to show the superiority of the proposed approach.